2021
DOI: 10.1177/11782218211050368
|View full text |Cite
|
Sign up to set email alerts
|

Patient Assessments of the Factors Facilitating and Impeding User Involvement During the First Phase of Substance Abuse Treatment

Abstract: User involvement in the first phase of treatment is essential for treatment satisfaction among patients with substance use disorders (SUDs). This study explores how patients perceive the first phase of specialized SUD treatment and identifies what promotes and inhibits user involvement. We used a qualitative approach, and semi-structured interviews were conducted with 14 informants admitted to a substance abuse treatment unit in central Norway. The analysis was inspired by a phenomenographical analysis approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…However, there has been little investigation into these relationships. A few previous findings suggest that family and peers are important sources for motivating and initiating recovery from substance use (Wenaas et al, 2021), particularly in emerging adulthood (Goodman et al, 2011). Several participants described family members, partners, and friends as important sources of motivation for recovery, including when family was not directly involved in their recovery process:…”
Section: Motivation For Recoverymentioning
confidence: 99%
See 3 more Smart Citations
“…However, there has been little investigation into these relationships. A few previous findings suggest that family and peers are important sources for motivating and initiating recovery from substance use (Wenaas et al, 2021), particularly in emerging adulthood (Goodman et al, 2011). Several participants described family members, partners, and friends as important sources of motivation for recovery, including when family was not directly involved in their recovery process:…”
Section: Motivation For Recoverymentioning
confidence: 99%
“…Studies of processes of recovery from problematic substance use have shown the importance of citizenship, supportive relationships, and experiencing social bonding and a sense of community (Bathish et al, 2017; Jason et al, 2001; Kelly et al, 2014; Moore et al, 2018; Mudry et al, 2019; Stevens et al, 2012; Wenaas et al, 2021). These studies have generally defined recovery as both a personal process and a social transformation.…”
Section: The Influence Of Communities On Recovery From Substance Use ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing awareness and education regarding SCD may equip providers to more effectively care for children and adults with SCD and may help to expand funding for research to inform efforts to mitigate the presence and negative effects of discrimination within healthcare settings. Drawing upon findings from other stigmatized illnesses such as HIV/ AIDS and substance use disorder, promising approaches to mitigate discrimination include ensuring appropriate descriptive language and naming of stigmatized populations within healthcare settings, listening to patient stories, and including and encouraging familial and/or community support [53,54].…”
Section: Discussionmentioning
confidence: 99%